Amino acid transporter LAT1 (SLC7A5) promotes metabolic rewiring in TNBC progression through the L-Trp/QPRT/NAD+ pathway - Margot Y. Fedoroff; Lei Zhao; Shaomin Wang; Alok Bhushan; Haifeng Yang; Karen M. Bussard; Stephen C. Peiper; Jun He (Journal of Experimental & Clinical Cancer Research)
Abstract Background Cancer cells uptake excessive nutrients by expressing higher levels of glucose and/or amino acid transporters to meet their increased energy demands. L-type amino acid transporter 1 (LAT1), is regarded as a cancer-specific transporter for the uptake of large neutral amino acids such as L-tryptophan. However, the mechanism by which LAT1 rewires cellular metabolism to promote cancer progression and chemoresistance have not yet been investigated. Methods The protein levels of LAT1, p-PKM2, and p-LDHA were determined in breast cancer tissue arrays by immunohistochemistry staining followed by survival analysis. The orthotopic breast cancer models in mice, syngeneic breast cancer models, and patient-derived xenograft (PDX) mouse models were used to study the effects of LAT1 inhibition in tumor growth and chemoresistance. Steady-state polar metabolite analysis was performed to profile changes in cellular metabolism by LC-MS. The pyruvate and lactate assays as well as the seahorse assay using LAT1 knockdown cells and control cells were conducted to evaluate cellular glycolytic activities. Results The LAT1 protein levels were positively correlated with poor survival in triple-negative breast cancer (TNBC) patients. LAT1 silencing resulted in reduced TNBC cell viability, proliferation, migration, invasion in vitro, as well as tumor growth in vivo. The knockdown of LAT1 reduced glycolytic activities via activating PKM2 and LDHA, two key glycolytic enzymes essential for cancer cell growth. Mechanistically, we demonstrated that LAT1 promoted de novo NAD + synthesis by facilitating L-tryptophan uptake and upregulating quinolinate phosphoribosyltransferase (QPRT), the rate-limiting enzyme in this pathway. This resulted in an increased cytosolic NAD+/NADH ratio, which enhanced the phosphorylation of pyruvate kinase M2 (PKM2) and lactate dehydrogenase A (LDHA), thus promoting TNBC tumor progression. Notably, upregulation of this pathway was observed in primary cells from doxorubicin (Dox)-resistant TNBC patient-derived xenograft (PDX) tumors and in Dox-resistant MDA-MB-231 cells. LAT1 inhibition sensitized resistant cells to Dox-induced cytotoxicity while supplementation of L-Trp/NAD + partially reversed the enhanced sensitivity to Doxorubicin induced by LAT1 knockdown. Furthermore, treatment with a LAT1-specific inhibitor JPH203 synergistically enhanced the efficacy of doxorubicin in TNBC cells. Conclusion These findings identify a novel role of LAT1 in promoting TNBC progression and chemo-resistance by amplifying the Warburg effect, positioning LAT1 as a promising therapeutic target for TNBC treatment.